Case report: Morphological changes evident after manual therapy in two cases of late-diagnosed developmental dysplasia of the hip - Fludder, Christian J.; Keil, Braden G.; Neave, Melissa J. (Frontiers in Pediatrics, 2023)
Background We describe two cases of late-diagnosed Developmental Dysplasia of the Hip (DDH) which demonstrated morphological femoroacetabular joint changes on x-ray after a 6-month trial period of manual therapy. Spontaneous resolution beyond six months of age without intervention is unlikely, improvement with bracing after 12 moa is unlikely and correction often requires aggressive intervention for normalisation. Case Presentation Two cases (13- and 30-months of age) with late-diagnosed DDH presented for conservative, non-bracing management. A trial of manual therapy was utilized over a 6-month period. Both cases demonstrated changes to femoroacetabular morphology as well as improvements in gross motor activity and lower extremity muscle tone. Conclusion Manual therapy, as an adjunct or alternative to static bracing, may be of benefit in individuals with late-diagnosed DDH not responding to bracing. Future prospective trials investigating this hypothesis are required.